2017
DOI: 10.1016/j.thromres.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group is associated with peripheral arterial disease in African Americans: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Introduction Peripheral artery disease (PAD) affects 8.5 million Americans and thus improving our understanding of PAD is critical to developing strategies to reduce disease burden. The objective of the study was to determine the association of ABO blood type with ankle brachial index (ABI) as well as prevalent and incident PAD in a multi-ethnic cohort. Methods The Multi-Ethnic Study of Atherosclerosis includes non-Hispanic White, African, Hispanic, and Chinese Americans aged 45–84. ABO blood type was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In our analysis, the ABO blood groups were neither a relevant risk factor for IS nor PAD. Conversely, the MESA study showed that the A blood group was associated with a greater risk of PAD in African Americans, although it was not significant in Chinese, non-Hispanic white or Hispanic Americans [39]. Since our study was performed in a Caucasian Finnish population, race/ethnicity factors might be involved in the observed differences.…”
Section: Abo Blood Groups and The Risk Of Is And Padmentioning
confidence: 55%
“…In our analysis, the ABO blood groups were neither a relevant risk factor for IS nor PAD. Conversely, the MESA study showed that the A blood group was associated with a greater risk of PAD in African Americans, although it was not significant in Chinese, non-Hispanic white or Hispanic Americans [39]. Since our study was performed in a Caucasian Finnish population, race/ethnicity factors might be involved in the observed differences.…”
Section: Abo Blood Groups and The Risk Of Is And Padmentioning
confidence: 55%
“…Estudios han mostrado que los individuos con el grupo sanguíneo O están protegidos contra el Síndrome Coronario Agudo (SCA) debido a su propiedad de coagulación más baja, mientras que una de las causas de SCA en individuos del grupo sanguíneo tipo No-O, podría ser el aumento de las propiedades de coagulación por el incremento del FvW (55) . También se ha visto comprometido en riesgo de aterosclerosis, en donde un mecanismo que involucra al grupo sanguíneo en estos procesos, es que las glicosiltransferasas ABO impactan a las Moléculas de Adhesión Celular (CAM), que son proteínas que se expresan en el endotelio vascular y que reclutan gran cantidad de leucocitos en los procesos inflamatorios, conllevando a daños en la vasculatura y la consecuente formación de trombos, además el aumento de estas proteínas en circulación se ha asociado con enfermedad de la arteria coronaria, infarto de miocardio y aterosclerosis (56)(57)(58)(59) .…”
Section: Proteína Adamts13 Y Relación Con Los Niveles Del Fvwunclassified
“…The frequency of atherosclerotic vascular disease was found to be increased in patients with blood groups other than group O. 68…”
Section: Introductionmentioning
confidence: 98%
“…The frequency of atherosclerotic vascular disease was found to be increased in patients with blood groups other than group O. [6][7][8] The TASC II classification is a widely used tool that shows the extent of atherosclerotic disease in the lower extremity and functions as a guide in the choice of treatment modality. In this classification, the disease is classified as TASC II A, B, C, and D considering severity of the disease.…”
Section: Introductionmentioning
confidence: 99%